Disaster Risk Management in Asia and the Pacific: Issues Paper - Asian Development Bank Institute (Tokyo) (Asian Development Bank Institute (ADBI), 2013)
This issues paper aims to help ADB DMC governments integrate Disaster Risk Management into their national developmental strategies and examine how emerging economies of Asia can cooperate to improve their disaster risk management practices, in view of increasing risks of compound disasters, climate change, and expanding production networks. It is intended to contribute to ADB's ongoing efforts to mainstream disaster risk management into its lending strategies, strengthen the governance for disaster risk reduction and disaster response in the region, improve the effectiveness of post-disaster reconstruction, and develop new financial instruments to help meet the costs of such activities through international, particularly regional, cooperation. Lessons from recent events both in pre-disaster risk mitigation and post-disaster response are identified and concrete recommendations for action are suggested.
hdl:11540/4180
Keywords: 330; Environmental Impact Assessment; Environmental Health Hazards; Environmental Guidelines; Environmental Services; Environmental Costs; Environmental Conditions; Environmental Action Plans; Environmental Cleanup; Project Evaluation; Katastrophe; Katastrophenschaden; Katastrophenschutz; Asiatisch-pazifischer Raum